The Correlation Between Students’ Habit in Watching English Movie and Their Vocabulary Mastery at the Eleventh Grade Students of SMAN 1 Raha - Ningsi, Pratiwi Sri Astuti; Nurnia, Nurnia; Agustina, Sitti (Journal of Teaching of English, 2021)
This study aims to find out whether there is a correlation between students’ Habits in watching English movies and their vocabulary mastery. This study applied a correlational design which employed quantitative research methods. The sample of this study was 32 students which were from XI IPA 7 in SMAN 1 Raha. The sampling was taken by purposive sampling method. This study conducted from January, 7 to 11 January 2020. The data were collected by using a questionnaire to measure the students’ frequency in watching English movies towards vocabulary and the vocabulary mastery test to know their vocabulary mastery. Moreover, the data were analyzed by using Pearson Product Moment Correlation with SPSS 16.0. The result indicates that there is a significant correlation between students’ frequency in watching English movie and their vocabulary mastery with r-obtained was 0.807 (p= 0.000). Further, it was categorized as a high correlation between the two variables. Moreover, this study shows that students’ habits in watching English movies have a positive correlation with their vocabulary mastery. It can be concluded that H1 is accepted and H0 is rejected. This indicates that there is a significant correlation between students’ habits in watching English movies and their vocabulary mastery.